2017
DOI: 10.1111/pai.12820
|View full text |Cite
|
Sign up to set email alerts
|

Early introduction of allergenic foods for the prevention of food allergy from an Asian perspective—An Asia Pacific Association of Pediatric Allergy, Respirology & Immunology (APAPARI) consensus statement

Abstract: Emerging evidence for the early introduction of allergenic foods for the prevention of food allergies, such as peanut allergy in Western populations, has led to the recent publication of guidelines in the USA and Europe recommending early peanut introduction for high-risk infants with severe eczema or egg allergy. Peanut allergy is, however, much less prevalent in Asia compared to the West. Varying patterns of food allergy are seen even within Asian countries-such as a predominance of wheat allergy in Japan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 92 publications
3
63
0
Order By: Relevance
“…The age at the time of the FPIES diagnosis varied according to the offending food and reflected, in general, the chronological pattern of food introduction in infants. Indeed, the presence of conflicting evidence, and the absence of contemporary national guidelines on food introduction, make many practitioners in Greece avoid the early introduction of foods like fish as some children can be allergic to them . As expected, we did not observe cases of soya FPIES, since soya and soya milk are rarely consumed in Greece.…”
Section: Discussionsupporting
confidence: 60%
“…The age at the time of the FPIES diagnosis varied according to the offending food and reflected, in general, the chronological pattern of food introduction in infants. Indeed, the presence of conflicting evidence, and the absence of contemporary national guidelines on food introduction, make many practitioners in Greece avoid the early introduction of foods like fish as some children can be allergic to them . As expected, we did not observe cases of soya FPIES, since soya and soya milk are rarely consumed in Greece.…”
Section: Discussionsupporting
confidence: 60%
“…18,19 These studies have also reported varying genetics within the population, concluding that peanut allergy may be linked to a microbial exposure and the environment. 20,21 Previous studies in Mexico were carried out among children with allergic diseases, where it was observed that peanut allergy prevalence was at 3.3%. 5 In our country, there are limited studies that have looked into the risk factors associated with peanut allergy; primarily, exposure and sensitization to pollens, oral allergy syndrome, job occupations, and contact with food proteins through direct skin contact, soaps or body lotions.…”
Section: Discussionmentioning
confidence: 99%
“…The Asia Pacific Association of Pediatric Allergy, Respirology & Immunology proposed a consensus statement on the early introduction of allergenic foods for the prevention of FA. 50 An observational birth cohort study in Icelandic children (n = 1304) prospectively followed from birth to 2.5 years with detailed questionnaires found that fish oil supplementation in infancy (6 months or younger) reduces the sensitization to food allergens and DBPCFC-confirmed FA by half at 2.5 years of age in a dose-dependent manner. 51 A recent study investigated the association between secondhand smoking (SHS) and pediatric food hypersensitivity using data from BAMSE, a longitudinal, population-based birth cohort of 4089 Swedish children born between 1994 and 1996.…”
Section: Pre Venti On and Control Of Food Allergymentioning
confidence: 99%